Transformasi Bisnis Melalui Business Process Reengineering: Tinjauan Literatur Terhadap Penerapan dan Dampaknya pada Berbagai Sektor - Hetria Hayyun Namirah; Ramadhan Fauzie Nugraha; Rudy Djuanda; Tri Aji Pujo Sembodo (Masyarakat Ekonomi Syariah Bogor, 2024)
Business Process Reengineering (BPR) became an important strategy for improving operational efficiency and effectiveness across various industrial sectors. In the era of globalization and increasingly fierce competition, companies were required to continuously innovate and enhance their operational efficiency. One approach that proved effective in achieving these goals was BPR. The purpose of this study was to present a comprehensive literature review on the implementation of BPR in various sectors, focusing on analyzing the factors that influenced the success and impact of BPR implementation. The research method employed was a literature review that explored the application of BPR in different contexts, including the creative economy, product distribution, healthcare, education, and the aviation industry. A literature review was conducted on 15 published studies from 2019 to 2024. The research showed that BPR focused not only on reducing costs but also on improving service quality and customer satisfaction. By utilizing information technology and collaborative approaches, companies overhauled their business processes to achieve better results. The findings of this review provided insight into the challenges and opportunities faced by organizations in implementing BPR, as well as recommendations for best practices in its implementation.